DEVELOPMENT OF E-LEARNING GAMIFICATION TO IMPROVE MATHEMATICS LEARNING RESULTS - Triswidrananta, Odhitya Desta; Pramudhita, Agung Nugroho; Wahono, Wahyu Tri; Wijaya, Elita Mega Selvia (Universitas Tribhuwana Tunggadewi, 2024)
One system that is widely used now is the e-learning system, which in the system brings the influence of transformation from conventional education to education with digital forms. This research uses the RD method. The results of black box testing by testing the functionality of the e-learning gamification learning system, the results obtained are as expected and all available features run well. The effectiveness of using a website-based gamification e-learning learning system in mathematics subjects is reviewed by comparing pre-test and post-test data. The learning media is said to be successful if the gain score value obtained is 0.71 or in the high category. To test the effectiveness of the e-learning learning system, researchers used the pre-test and post-test method on 15 students of class VI-C SDN Purwantoro 1 Malang City which resulted in a difference in value or the final result of the test in the form of calculating the gain score value by obtaining a value of 0.71 which is classified as a high category. Based on the research that has been done as a whole, it can be concluded that researchers have successfully implemented a website-based gamification e-learning learning system to improve student learning outcomes.